Poder e relações políticas na educação: o método Lancaster no ensino público do Espírito Santo (1827 a 1860) - Ferreira, Dirce Nazaré de Andrade (2015)
This study deals with a historical survey that addressed the Lancasterian Method in nineteenth-century public education in the Province of the Holy Spirit. Analyzes the schooling between 1827 to 1871 for the presence of Lancasterian Method and strategies. Addresses the disciplinary techniques contained in the work of Joseph Lancaster from his works, the original sources of the nineteenth century, made available by the British School of Hitchin Museum in London. Describes the structures and pedagogical materials described by Lancaster to extend teaching and boost enrollment in eight. Aims to investigate the power and political relations that were inserted in education by Lancasterian method, analyze policies and pedagogical practices developed in education and discuss the power relations contained in the official discourse of the agents responsible for education in the Province of the Holy Spirit. Describes the method Lancasterian structures and teaching materials such as classrooms, sand boxes, slate boards, the lancasterianos commands, punishments and rewards. Demonstrates that the rationality of the method was inserted in post-independent Brazil to form a system of education supported by the monarchical state and the Catholic church. Describes Gennaro da Cunha Barbosa and Law Reform Couto Ferraz as legislative measures that formalized the method Lancasterian in Brazil as a strategy to discipline, orderly preach civility, love of country and religious devotion. Describes education in the Holy Spirit Province from 1827 to 1871 through the speeches of Presidents of the Province, demonstrating adherence to Lancasterian method. Discusses the Holy Spirit and the politics that gave perspectives on education to strengthen and discipline the people. Describes the primary sources contained in the Public Archives and demonstrates Lancasterian Method in newspapers of the nineteenth century, and in the Rules Schools of First Letters of 1871. In technical visit, makes a comparison between the in situ primary sources lancasterianas the Holy Spirit and sources archived at the British Museum School, Hitchin, UK, demonstrating that there are similarities and differences between the two loci Lanacasterino Method and political strategies were incorporated in education as a way of exercising power.